Transformational responses to climate change: beyond a systems perspective of social change in mitigation and adaptation. (15th January 2016) - Gillard, Ross; Gouldson, Andrew; Paavola, Jouni; Van Alstine, James
Abstract : There is a growing imperative for responses to climate change to go beyond incremental adjustments, aiming instead for society‐wide transformation. In this context, sociotechnical (ST) transitions and social–ecological (SE) resilience are two prominent normative agendas. Reviewing these literatures reveals how both share a complex‐systems epistemology with inherent limitations, often producing managerial governance recommendations and foregrounding material over social drivers of change. Further interdisciplinary dialogue with social theory is essential if these frameworks are to become more theoretically robust and capable of informing effective, let alone transformational, climate change governance. To illustrate this potential, ideas from Deleuze and Guattari's political writing as well as other approaches that utilize the notion social fields (as opposed to sociosystems) are combined to more fully theorize the origins and enactment of social change. First, the logic of systems is replaced with the contingency of assemblages to reveal how pluralism, not elitism, can produce more ambitious and politicized visions of the future. In particular, this view encourages us to see social and ecological tensions as opportunities for thinking and acting differently rather than as mere technical problems to be solved. Secondly, the setting of social fields is introduced to situate and explain the power of ideas and the role of agency in times of uncertainty. The potential of such insights is already visible in some strands of climate change mitigation and adaptation research, but more needs to be done to advance this field and to bring it into dialogue with the mainstream systems based literature. WIREs Clim Change 2016, 7:251–265. doi: 10.1002/wcc.384 This article is categorized under: Climate and Development > Social Justice and the Politics of Development Social Status of Climate Change Knowledge > Climate Science and Decision Making